Estrategia didáctica aprendizaje basado en problemas y desarrollo de competencias investigativas en estudiantes de Segunda Especialidad en Tecnología Educativa - Alva Diaz, Jorge Enrique (2020)
The research we present is about the study of Problem-based Learning described as a didactic strategy and its relationship with the development of the research competencies of the students of the third term of the specialty Teaching - Learning Curriculum of the Program of Second specialty in Educational Technology of the National University of Trujillo. The academic importance of the research work lies in applying The Problem-based learning strategy to develop the research competencies of the third term students in the Educational Technology Research I subject area of the Second Specialty Program in Educational Technology of the National University of Trujillo. The methodology applied was based on the deductive hypothetical method, with a simple descriptive research design, where the sample was 36 students specialized in Teaching - Learning Curriculum, enrolled in the Educational Technology Research I subject area. The results obtained are that it is possible to verify the correlation between Problem-based learning and the development of research competencies.